Review of the Jihadi and Mystical Services of Maulana Muhammad Shoaib Tordheri (Khairulummah, 2021)
Allah has promised to protect Islam. That is why Allah created scholars and Sufis in different periods that served Islam and preached Islam. The preaching and propagation of Islam in India is due to these Sufis. They left their territories and came to India. One of these scholars and Sufis is Maulana Muhammad Shoaib Tordheri, known as Shaikh Sahib. He was the Shaikh of Moulana Abdul Ghafoor (Swat Babaji), that is the most famous Sufi in Swat Khyber Pakhtonkhwa and Shaikh of the Moulana Abdul Rahim Saharan Puri.  Moulana Muhammad Shoaib was not a scholar and sufi, he was also a mujahid. He was martyred while fighting against the Sikhs in 1823 A.D. He wrote a book about Sufism. In his book he wrote about seeratul Nabi and companion of Prophet Muhammad S.A.W. After that he discussed circumstances and sayings of Sufis of the all four series (Naqshbandia, Qadria, Cheshtia and Saharwardia) of Sufism. He also described the attributes of the perfect Peer.
Keywords: Jahadi, Tordheri,Sufis,Swat Babaji